THE INFLUENCE OF THE MARKETING MIX ON DECISIONS PURCHASE OF ITEMS ON THE SHOPEE APPLICATION - Fahrozi Silaban; Satria Mirsya Affandy Nasution (Proceeding International Seminar of Islamic Studies, 2022)
This study is to determine and analyze the effect of Product, price, place, promotion, physical evidence variables on purchasing decisions on the Shopee Application. Either partially or simultaneously. This study uses a quantitative approach. The analysis technique used is a multiple linear analysis technique. The results of this study conclude that partially there is a significant effect of the Product variable on the Purchase Decision of the Shopee Application on FEB Students, University of Muhammadiyah North Sumatra. The results of this study conclude that partially there is a significant effect of the price variable on the Purchase Decision on the Shopee Application for FEB Students, University of Muhammadiyah North Sumatra. The results of this study conclude that partially there is a significant effect of the Place variable on the Purchase Decision on the Shopee Application for FEB Students, Muhammadiyah University, North Sumatra. The results of this study conclude that partially there is no significant effect of the promotion variable on the Purchase Decision on the Shopee Application for FEB Students, Muhammadiyah University of North Sumatra. The results of this study conclude that partially there is no significant effect of the physical evidence variable on the Purchase Decision on the Shopee Application for FEB Students, Muhammadiyah University of North Sumatra. The results of this study conclude that there is a simultaneous and significant effect of Product, Price, Place, Promotion and Physical Evidence on the Shopee Application on FEB Students, Muhammadiyah University of North Sumatra. The results of the regression calculation can be seen that the coefficient of determination (R square) obtained is 0.362, this result means that 36.2% of the Purchase Decision variables can be explained by the Product, Price, Place, Promotion and Physical Evidence variables while the remaining 63.8% explained by other variables not examined.